Community experiences on prevention, preparedness and recovery of the flood disaster in cultural and local wisdom context - Nurumal, Mohd. Said; Daud, Azlina; Samsuddin, Niza; Aung, Khin Thandar (IIUM Press, 2019)
Objective: This qualitative descriptive study, underpinned by the naturalistic inquiry, explored the experiences of each level of households during and after the devastating flood disaster occurred in Kelantan, based on their cultural and local wisdom context. Methods: Three most affected districts were selected in this research: Gua Musang, Kuala Krai and Kota Bharu. Data gathered in this study was the researcher himself, in-depth interview guides, tape and video recording of interviews and a diary of the study for the duration of four months. Individuals from each level of the household were taken as a key informant. Results: Based on the data gathered from key informants, the prominent features of this research are: community preparedness in dealing with floods, uneven distribution of rains, unpredictable flood water level, inadequate food supply and preparation, the proper salvation of community in self rescue, effectiveness of communication during evacuation, inappropriate manner, water rise indication at a certain area and signs of nature. Conclusion: These findings were reflected in the experiences together understanding the value of local wisdom and cultural faced by key informants dealing with the flood disaster and it would be used in creating appropriate programs on preparation in dealing with such disaster in the future.